Pengaruh Social Media Marketing dan Electronic Word of Mouth Terhadap Purchase Decision - Jihan Sulaiman; Yunika Ardianna Br Sebayang; Sulaiman, Fahmi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine the effects of social media marketing (SMM) and electronic word of mouth (e-WOM) on purchase decisions at Treat Coffee and Beans. The study population consisted of 2,623 followers of the Coffee Shop Medan social media account. The sample was taken using purposive sampling with specific criteria and calculated using the Slovin formula, resulting in 100 respondents. This study employs a quantitative approach, utilizing a questionnaire on SMM, e-WOM, and purchase decisions that have been validated for validity and reliability. Data analysis was conducted using multiple linear regression. The results of the study indicate: (1) SMM and e-WOM together have a significant influence on purchase decisions (calculated F = 79.003 > table F = 2.41; sig. 0.000 < 0.05); (2) SMM has a positive and significant influence on purchase decisions (T calculated = 5.198 > T table = 2.365; sig. 0.000 < 0.05); (3) e-WOM also has a positive and significant effect on purchase decisions (T calculated = 2.98 > T table = 2.365; sig. 0.001 < 0.05).